Rational design of boron-containing co-doped graphene as highly efficient electro-catalysts for the nitrogen reduction reaction. Issue 43 (27th October 2021) - Ouyang, Wencheng; Zhi, Qiuming; Gong, Lele; Sun, Hao; Liu, Minghui; Zhang, Jing; Han, Xiao; Xia, Zhenhai; Zhang, Lipeng
Abstract : The electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions has been proposed as a sustainable alternative for nitrogen fixation and ammonia production in environmental and renewable energy fields. Abstract : The electrocatalytic nitrogen reduction reaction (NRR) under ambient conditions has been proposed as a sustainable alternative for nitrogen fixation and ammonia production in environmental and renewable energy fields. Carbon-based materials have been demonstrated as a kind of potential catalyst for the NRR. Doping heteroatoms is a feasible strategy to improve the catalytic activity of carbon-based catalysts. The doped element was usually determined by trial-and-error methods. Herein, using density functional theory (DFT) methods, we explored the NRR catalytic activity of p-block dual-element doped graphene nanoribbons. An intrinsic descriptor was found and used to characterize the catalytic activity of dual-element doped graphene nanoribbons in the NRR. The relationship between the descriptor and catalytic activity was established, which helps us screen out the optimal doped structures and provides design principles for exploring excellent NRR catalysts. This work not only explores the inherent law for the catalytic performance of co-doped graphene, but also provides a theoretical guide to experimentally explore excellent NRR catalysts under ambient conditions.